Water Hyacinth Planthopper (suggested common name) Megamelus scutellaris Berg (Insecta: Hemiptera: Delphacidae) - Jermiah Foley; Carey R. Minteer (EDIS, 2020)
Originally published on the Featured Creatures website at http://entnemdept.ufl.edu/creatures/beneficial/bugs/Megamelus_scutellaris.htm